Secrecy Performance of Overlay Cognitive Radio Inspired NOMA With Untrusted Secondary User - Swathi Priya Indraganti; Suseela Vappangi (IEEE Access)
In this paper, we investigate the integration of physical layer security (PLS) and cognitive radio (CR) technologies with non-orthogonal multiple access (NOMA) to enhance spectral efficiency (SE) and security in fifth generation (5G) and beyond wireless networks. We propose a novel downlink overlay CR inspired NOMA (CR-NOMA) system, where a secondary base station (SBS) relays data from a primary base station (PBS) to a primary destination (PD) while simultaneously transmitting its own data to a secondary destination (SD). Our analysis focuses on investigating the performance of this system in the presence of untrusted users, deriving novel closed-form solutions for various performance metrics such as ergodic capacity (EC), throughput, connection outage probability (COP), secrecy ergodic capacity (SEC), intercept probability (IP), effective secrecy throughput (EST), and secrecy outage probability (SOP) under different channel constraints. In addition, we present an optimal power allocation (OPA) strategy that enhances secrecy performance of the proposed system over Rayleigh fading channel. The simulation results of our work demonstrate the effectiveness of the proposed system in maintaining confidentiality and achieving high SE. Furthermore, for enhancing the performance of the overall system, we utilize maximal ratio combining (MRC) and selection combining (SC) diversity methods for analyzing the received signal at the PD. To this end, to enhance the performance of the proposed model for both single and multiple antenna systems, artificial noise (AN) jamming signals, asymptotic analysis, and diversity schemes are presented. We validate our analytical findings through MATLAB based simulations, showcasing the accuracy of our results. This paper contributes to the development of secure and efficient wireless communication systems, addressing the growing concerns of security in 5G and beyond networks.